(untitled) - Larissa Cerignoni Benites; Samuel Souza Neto; Marina Cyrino; Mariane Gimenes Costa; Julia Jacomini Costa (Universidade Estadual Paulista Júlio de Mesquita Filho, 2011)
In the concern with the process of professional training, the look of this study focused the process of continued education, particularly an extension course called "Escola de Educadores", which has as its theme the understanding of fraternity and education for peace as pedagogical possibilities. Thus, the research's aim was to clarify the course proposal and determine the participants' materials production and the relation to the theme concerned. This is a study which relies on the qualitative analytical approach, emphasizing the exploratory study. As a result, one indicates the course has a structure coherent with its objectives and presents pedagogical actions planned and systematized, with a theoretical and/or practical design which are not included in the syllabus of the regular undergraduate or graduate courses, allowing the "pedagogical rethinking" of the teacher. On the materials production, one observes the incorporation of themes worked out in the reading course by the concluding course monographs and innovative initiatives in the internships. As a concluding remark, one understands the extension course presents itself as a training opportunity, but it is also a universe of new experiences and challenges.